Measuring air time for runners in real time - ANDERSSON, ELSA; LINDH, KRISTOFFER (My University, 2020)
Running has always been a popular way to exercise and one way to improve the running technique and prevent injury is to adjust the gait. In order to improve the gait the runner must gain knowledge about his/her own gait. In this master’s thesis, a system has been developed that measure the time when a runner is in the air while running. The data about air time should be available to the runner with such a short delay that the runner could immediately adjust the gait. The system should also be light weight and small enough to be carried around whilst having a low power consumption in order to minimize battery size. The system has been developed using one microcontroller and two inertial measurement units. A functional algorithm that can determine gait events in order to measure air time with an accelerometer has been developed. The precision of the system was low and needs to be adjusted in order to be useful to a runner. The small size of the system makes it wearable and due to the low power consumption, the system could be powered for eight hours with a small button cell battery.
Keywords: Gait event; Inertial measurement unit; Microcontroller